The Evaluation of Cooperation in the Management of Health Promotion and Disease Prevention Budget between the Ministry of Public Health and the National Health Security Office - Wadwongtham, Aree (Journal of Health Science of Thailand, 2018)
This study was aimed at evaluating the quality of the Health Promotion and Disease Preven-tion Plans of Provincial Pubic Health Offices as the immediate product of cooperation in themanagement of the Health Promotion and Disease Prevention Budget between the Ministry of Pub-lic Health (MOPH) and the National Health Security Office (NHSO) in fiscal year 2008 under theCIPP model. The results of quality analysis of the plans collected from 72 provinces with established crite-ria revealed that the plans were classified into three groups: high, moderate and low, at the propor-tion of 2639, 63.89 and 9.72 percent respectively. In details, the 77.78 percent of the plans coveredurgent policies of MOPH, 97.72 percent covered vertical programs, 95.83 percent covered 14 riskfactors determined by NHSO. Of the 72 provinces, 81.94 percent had integrated plans and 66.67percent had potential development plans for health promotion and disease prevention. These werethe results of good objectives of the project which were in line with the policies of the governmentand MOPH, particularly with respect to socio-economic situations, decentralization trends and newbudget allocation guidelines. This project had good administrative concepts and a clear process ofimplementation. There was also a meeting for provincial health officials concerned to clarifythe policy and implementation procedures, followed by monitoring and evaluation of the budgetmanagement. Case studies were conducted on three randomly selected provinces, each with high, moderateand low quality of plan, respectively. It was found that there was no difference in the process of plandevelopment, but the one with a high-quality plan had a systematic and formal strategic planningprocess using various techniques. The weaknesses of this project were late policy implementation and redundant orders fromboth MOPH and NHSO. The provinces participating in the case studies suggested that there should be a review of rolesand missions of MOPH and NHSO, all policies from all departments should have been integrated bythe ministry before being disseminated to provinces for implementation, the continuity of the policyshould have been maintained, and the performance indicators and reporting systems should havebeen streamlined. These should have helped reduce workload, so health care professionals wouldbe able to devote more time and efforts to services. In addition, there should be a mechanism for monitoring the implementation of the plans and astudy on the effect of health promotion and disease prevention programmes.